2013
DOI: 10.1127/0029-5035/2013/0079
|View full text |Cite
|
Sign up to set email alerts
|

The genus Sphagnum L. in Turkey - with S. contortum, S. fallax, S. magellanicum and S. rubellum, new to Turkey and Southwest Asia

Abstract: Four species, S. contortum, S. fallax, S. magellanicum and S. rubellum are recorded for the first time from Southwest Asia respectively Turkey, increasing the total known number of species to 22 (resp. 21 from Turkey). Five species (S. capillifolium, S. girgensohnii, S. inundatum, S. teres, S. warnstorfii) are recollected after more than 100 resp. 40 years. In addition, first hints to the occurence of Oxycocco-Sphagnetea communities (e.g., Sphagnetalia magellanici) in Turkey are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…is a fairly widespread species (Kyrkjeeide et al 2015), reported from most European countries, European Russia, temperate Asia (Siberia, Russian Far East, Middle Asia, China, Mongolia, and Japan) and North America (Canada and USA), but it is known to be very rare in mountain areas (Ignatov et al 2006;Séneca and Söderström 2009;Kyrkjeeide et al 2015). In the Caucasus Mountains, the species is reported from Armenia (Manakyan 1995), Georgia (Chikovani and Svanidze 2004), and Russia, namely: one record from Karachay-Cherkess Republic (Sofronova et al 2012) Kırmacı and Kürschner (2013)]; south of Sürmene-Köprübaşı, Ağaçbaşı Yayla Ayı Yatağı locality, 25 August 2016, leg. M. Kırmacı (MKIR 7265).…”
Section: Rhynchostegiella Tubulosamentioning
confidence: 99%
“…is a fairly widespread species (Kyrkjeeide et al 2015), reported from most European countries, European Russia, temperate Asia (Siberia, Russian Far East, Middle Asia, China, Mongolia, and Japan) and North America (Canada and USA), but it is known to be very rare in mountain areas (Ignatov et al 2006;Séneca and Söderström 2009;Kyrkjeeide et al 2015). In the Caucasus Mountains, the species is reported from Armenia (Manakyan 1995), Georgia (Chikovani and Svanidze 2004), and Russia, namely: one record from Karachay-Cherkess Republic (Sofronova et al 2012) Kırmacı and Kürschner (2013)]; south of Sürmene-Köprübaşı, Ağaçbaşı Yayla Ayı Yatağı locality, 25 August 2016, leg. M. Kırmacı (MKIR 7265).…”
Section: Rhynchostegiella Tubulosamentioning
confidence: 99%
“…Sphagnum includes approximately 120 species, commonly known from boggy wetland habitats (Daniels and Eddy 1985;Kırmacı and Kürschner 2013). Currently, 23 taxa in Sphagnum have been recorded for Turkey, this new record brings the total to 24 (Abay et al 2009;Kırmacı and Kürschner 2013;Tonguç Yayıntaş 2013;Abay and Keçeli 2014).…”
Section: World Distributionmentioning
confidence: 99%
“…Currently, 23 taxa in Sphagnum have been recorded for Turkey, this new record brings the total to 24 (Abay et al 2009;Kırmacı and Kürschner 2013;Tonguç Yayıntaş 2013;Abay and Keçeli 2014).…”
Section: World Distributionmentioning
confidence: 99%
“…Important and considerable investigations have thus far been carried out in Trabzon province (Gökler, 1998;Papp, 2004;Townsend, 2005;Lara et al, 2010;Batan and Özdemir, 2011;Kirmaci et. al., 2012;Kırmacı and Kürschner, 2013;Özdemir & Batan, 2017a), and a few papers were also noted from Giresun province (Özdemir and Baydar, 1997;Özdemir, 1999;Özdemir, 2001a, b;Özdemir and Koz, 2005;Özdemir and Koz, 2006;Özdemir and Koz, 2007;Özdemir and Batan, 2008;Özdemir, 2008;Kırmacı and Kürschner, 2013;Özdemir and Batan, 2017b). Any detailed bryofloristic studies have not noted from the Sis Mountain so far.…”
Section: Introductionmentioning
confidence: 98%